Respuesta :
We first determine the term-to-term rule in this sequence.
[tex]3.1-2.5=0.6[/tex]
[tex]3.7-3.1=0.6[/tex]
[tex]4.3-3.7=0.6[/tex]
We see that the term-to-term rule is adding 0.6 and the sequence is an Arithmetic sequence.
The formula to find the [tex] n^{th} [/tex] term in an Arithmetic sequence is given
[tex]dn+ 0^{th} term[/tex], where d is the difference between term
Hence for the sequence above, the equation is [tex]0.6n+1.9[/tex]
[tex]3.1-2.5=0.6[/tex]
[tex]3.7-3.1=0.6[/tex]
[tex]4.3-3.7=0.6[/tex]
We see that the term-to-term rule is adding 0.6 and the sequence is an Arithmetic sequence.
The formula to find the [tex] n^{th} [/tex] term in an Arithmetic sequence is given
[tex]dn+ 0^{th} term[/tex], where d is the difference between term
Hence for the sequence above, the equation is [tex]0.6n+1.9[/tex]
Answer:
a. f(n)=0.6n + 1.9
Step-by-step explanation:
got it right in edgenuity 2020. :)